Overview of heat treatment and surface engineering, influences of surface finishing on hot–work tool steel. (1st January 2015) - Rosso, Mario; Peter, Ildiko; Gobber, Federico Simone
Due to high resistance, toughness, formability and wear resistance, the use of both ferrous and non ferrous alloys is widespread in automotive, tools and die manufacturing, high–temperature applications (engines, valves, nozzles and turbines), oil/gas and energy production plants. The destructive effects of wear, corrosion, high temperature working conditions and their synergic action cost 100 billion Euros each year and most problems affect the surface of a component. Die casting is characterised by harsh conditions for the die which has to resist to all the damaging mechanisms proposed and molten aluminium alloy is a potential corrosive environment for steel. Periodical heating/cooling cycles can lead to thermal fatigue damaging of the die. In this paper, the relation between the surface finishing of a hot–work tool steel used in die casting industry and its damaging mechanism during service was considered and studied.